Play and the politics of reading: the social uses of modernist form - Armstrong, Paul B. (Cornell University Press, 2005)
"Reading is socially useful, in Paul B. Armstrong's view, and can model democratic interaction by a community unconstrained by the need to build consensus but aware of the dangers of violence, irrationality, and anarchy. Reading requires mutual recognition but need not culminate in agreement, Armstrong says; instead, the social potential of reading arises from the active exchange of attitudes, ideas, and values between author and reader and among readers. Play and the Politics of Reading, which has important implications for education, draws on Wolfgang Iser's notion of free play to offer a valuable response to social problems."--Jacket